Post-Truth Thinking: A Critical View - Dr. Mario González Arencibia; Hernández Velázquez , Miguel Ramón (IJRDO - Journal of Social Science and Humanities Research, 2022)
The objective of this article is the critical analysis of the thought associated with the idea of the "post-truth era" from a Marxist perspective, considering economic, political, and ideological factors. The study was carried out through the inductive and deductive and historical-logical methods, expressed in the systematization of texts. The fundamental result was the identification of the epistemological gaps of the subject, which allowed to advance in the critique of the studied phenomenon. The central conclusion is that post-truth is a phenomenon with an absence of rigor and integrity, ideologically biased by supporters of deception, who respond to business models associated with manipulation, in a political context, in which the truth is defined from the predominant power relations of the international financial oligarchy. With the proliferation of thinking about the "post-truth era", an attempt is being made to build a mentally immobilized global society, an aspect based on the assumptions of the fourth generation war, which has as its axis the transnational monopoly power, economically, politically and ideologically. What we are dealing with is the manipulation of psychological factors that ignotize human consciousness, using the electronic-informatics revolution.